Praktik Jual Beli Ikan Sistem Jizaf Dalam Perspektif Hadis: (Studi Kasus di Kaduara Barat Pamekasan) - Wida, Widadatur Rahmah; Farah Ubaidillah, Mohammad (El Nubuwwah Jurnal Studi Hadis, 2023)
Jizaf is buying and selling which is done by stacking goods without measuring, calculating and adding up the quantity. So it can cause uncertainty in the quantity. This article aims to understand the practice of buying and selling the pile system (jizaf) in Kaduara Barat Pamekasan. Based on this, there are two problems that are the main study in this research, namely: first, what is the practice of buying and selling fish using the jizaf system in Kaduara Barat Pamekasan. Second, what is the review of the hadith on the practice of buying and selling fish using the jizaf system in Kaduara Barat Pamekasan. This research is field research with a case study approach using qualitative methods. Primary data sources were obtained through interviews, secondary data came from literature review. Research result; (1) The practice of buying and selling jizaf in Kaduara Barat Pamekasan is carried out in several steps. First, the fishermen unload the fish, then transport them to land. Second, fishermen sort the fish. Third, the process of negotiating prices and payments. Fourth, the fishermen store the fish in boxes, and finally the contractor transports the boxes containing the fish. (2) Based on a review of the hadith, jizaf buying and selling transactions may be carried out provided they fulfill the legal requirements. Buying and selling fish using the jizaf system in Kaduara Barat Pamekasan in terms of harmony (contract, person with the contract, object and exchange value) has been fulfilled. However, in terms of the conditions for realizing harmony, there are things that are not appropriate. Namely, the object of the contract in the jizaf system fish buying and selling in Kaduara Barat Pamekasan contains elements that are not permitted, such as the occurrence of an element of fraud in the object of the goods being stacked.